SIKAP MAHASISWA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG TENTANG MITIGASI BENCANA GEMPA DAN TSUNAMI - 332-338 , Rafika S (CIVED, 2014)
ABSTRACT   Faculty of Engineering State University of Padang is located on an earthquake and tsunami hazard zone. Otherwise, the attitude and curiosity of students at Faculty of Engineering of State University of Padang about disaster mitigation is still lacking. In addition, a poor level of knowledge implementation about disaster mitigation by the government and related institutionsis also still lacking. This research aimed to describe the attitude of students at Faculty of Engineering State University of Padang toward the earthquake and tsunami disaster mitigation in Padang city. The type of data in this research was a primary data which was obtained directly from the object of the research by proposing a questionnaire to the students and a secondary data from many books and articles related to the research. The technique of data collection that used in this research was survey and documentation. The technique of data analysis was performed by descriptive statistical analysis by using the percentage formula and then translated into a narrative form. The conclusion of this research is the student attitude toward the earthquake and tsunami disaster mitigation was good with percentage 72,4%. Key word: Attitude, Disaster, Mitigation